2020
DOI: 10.35691/jbm.0202.0129
|View full text |Cite
|
Sign up to set email alerts
|

Use of Different Agro-wastes in the Cultivation of Pleurotus ostreatus (Jacq.) Kummer

Abstract: Agro-wastes are abundant in both rural and urban areas and when carelessly disposed off to the environment by dumping or burning, they lead to environmental pollution, and consequently to health hazards. Growing of edible mushroom on these wastes can contribute to decrease in environment pollution. This work investigated the growth and yield of Pleurotus ostreatus on different agro-wastes: plantain midrib (PM), corn straw (CS), sugarcane bagasse (SB) and their combinations (PM+CS, PM+SB, CS+SB, CS+PM+SB) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Huang et al [59] utilized rice straw, while Wiafe-Kwagyan et al [71] additionally used rice bran and husk mixtures supplemented with different percentages of CaCO 3 . Corn straw and sugarcane bagasse were mixed (50%:50%) in combination with plantain midrib in order to find out the best substrate for cultivation [72], while corncob alone and in the mixture with finger millet straw and bamboo waste was used in the following study [73].…”
Section: Composition Of Food Waste Substrates Used For Mushroom Culti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al [59] utilized rice straw, while Wiafe-Kwagyan et al [71] additionally used rice bran and husk mixtures supplemented with different percentages of CaCO 3 . Corn straw and sugarcane bagasse were mixed (50%:50%) in combination with plantain midrib in order to find out the best substrate for cultivation [72], while corncob alone and in the mixture with finger millet straw and bamboo waste was used in the following study [73].…”
Section: Composition Of Food Waste Substrates Used For Mushroom Culti...mentioning
confidence: 99%
“…First of all, the studies include biological efficiency of substrate utilization (BE) as the most valuable parameter that involves the yield of the cultivated fruiting bodies per kg of substrate on a dry weight basis [27][28][29]32,36,37,39,52,53,55,58,59,65,66,68,70,71,73]. This parameter is followed with mycelium running rate in bags (mm/day) [27,28,52,70], total mushroom yield (g) [27,28,32,37,54,58,65,[67][68][69][71][72][73], time required for completion of mycelium running (days), time required for primordia appearance and harvesting (days) [27][28][29]35,37,39,54,58,60,64,70,72,73]. On...…”
Section: Composition Of Food Waste Substrates Used For Mushroom Culti...mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be influenced by several factors such as the types of mushroom species, the used substrate, and the level of nitrogen available in the growth substrate (Belletini et al 2019). Currently, the number of studies that focus on the utilization of lignocellulosic substrates are increasing (Iwuagwu et al 2020;Nongthomban et al 2021). Ganash et al (2021) demonstrated that Pleurotus species are very effective in breaking down lignocellulosic residues making it a suitable mushroom to be cultivated on lignocellulosic substrates (Figure 1).…”
Section: Cultivation and Analysis Of P Ostreatus Nutritional Contentmentioning
confidence: 99%
“…This organic bulk can pollute the environment in many cases especially the lignocellulosic components as they are not readily degraded by organisms (Hatakka 1994;Philippoussis 2009). Waste materials from agriculture and industry can be used to grow mushrooms (Abid et al 2020;Iwuagwu et al 2020). Mushrooms are macrofungal fruiting bodies that are extremely rich in flavor and do not have high calories but are rich in vitamins, minerals, and proteins (Mubasshira et al 2020).…”
Section: Introductionmentioning
confidence: 99%